2019
DOI: 10.1097/jcn.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Factors Associated With Better Self-care in Heart Failure Patients With and Without Mild Cognitive Impairment

Abstract: Background A decline in cognition may limit patients' ability to effectively engage in self-care in those with heart failure (HF). However, several studies have shown no difference in self-care between HF patients with and without cognitive impairment. This may indicate that there are more salient factors associated with self-care in HF patients with cognitive impairment compared with those without cognitive impairment. Objective The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Sociodemographic variables are only a small proportion of the factors known to influence behavior. Clearly factors such as access to care and social support are important determinants of self-care in persons with HF (Lee et al, 2019). Future studies that capture the full range of SDH indicators and are grounded in theory are warranted to explain the intricate relationships between SDH and HF self-care behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic variables are only a small proportion of the factors known to influence behavior. Clearly factors such as access to care and social support are important determinants of self-care in persons with HF (Lee et al, 2019). Future studies that capture the full range of SDH indicators and are grounded in theory are warranted to explain the intricate relationships between SDH and HF self-care behavior.…”
Section: Discussionmentioning
confidence: 99%
“… 22 This association is not surprising, because self-care behaviors require memory and cognitive skills (eg, remembering to take medications and understanding symptom changes). 23 , 24 A study using magnetic resonance imaging–based diffusion tensor imaging revealed that lack of brain tissue integrity in executive function regulatory regions was associated with poorer HF self-care maintenance and self-care management. 25 Poor self-care may be responsible for the higher mortality rates 26 and increased risk of 30-day rehospitalization in persons with HF and cognitive impairment.…”
Section: Problem Person and Environmental Factorsmentioning
confidence: 99%
“…Tables 1 , 2 summarize the main characteristics of the 21 included studies. Studies were conducted in Asian regions, including China ( n = 16) ( 19 , 37 – 50 , 52 ), Japan ( n = 3) ( 34 , 35 , 51 ), Korea ( n = 1) ( 36 ), and Singapore ( n = 1) ( 19 ). Nine of the 21 included studies ( 19 , 34 , 35 , 37 , 40 , 42 , 50 – 52 ) used the MMSE as a cognitive screening tool, while there were 14 studies ( 19 , 36 , 38 , 39 , 41 , 43 – 49 , 52 , 53 ) used the MoCA and 1 study ( 51 ) used the Mini-Cog.…”
Section: Resultsmentioning
confidence: 99%